Bentuk Media Komunikasi Perempuan Lurah dalam Mensosialisasikan Penertiban Bangunan Liar untuk Menciptakan Keamanan Lingkungan Kota Bekasi - Harahap, Hamida Syari; Hubeis, Aida Vitayala S; Saleh, Amiruddin; Matindas, Krishnarini (Jurnal Keamanan Nasional, 2021)
The purpose of the study was to analyze the form of village headwoman communication media in socializing the control of illegal buildings (bangli) in the city of Bekasi. Forms of communication media used by women headmen are direct communication and indirect communication. Forms of direct communication media such as socialization, meetings, recitation, cadres, sharing, telling stories, chatting together, community forums, gathering in the field, dawn around, and indirect forms of communication media are utilizing media including SMS, letters, leaflets, telephones, invitations, and WhatsApp. The study was conducted in Bekasi City during August-October 2018. The study used a qualitative approach. The data analysis technique used NVivo 12. The results showed that the form of communication of Women headmen was situational. WhatsApp is the communication medium most frequently used by Women headmen to communicate with their citizens. This is due to the activities of the women's headmen so dense that the information conveyed arrived in seconds and was cheap. WhatsApp supports the women's headman in controlling the residents’ living environment and is not limited by space and time. WhatsApp is a media that is considered to be very fast in helping village women to convey information and solve problems faced by residents so that it can be handled directly even though the female village head is not in the location. As many illegal buildings that stand on public facilities interfere with environmental security. To carry out environmental control, the female head of the village does not have to visit all regions but can share information and tasks with RT, RW, community leaders, and community organizations using WhatsApp.